Chlorogenic Acids Inhibit Adipogenesis: Implications of Wnt/β-Catenin Signaling Pathway - Mengting Liu; Jian Qin; Jing Cong; Yubin Yang (International Journal of Endocrinology)
In our previous in vitro study, we found that chlorogenic acid (CGA) inhibited adipocyte differentiation and triglyceride (TG) accumulation, but the underlying mechanism is still unclear. Accumulative genetic evidence supports that canonical Wnt signaling is a key modulator on adipogenesis. Methods. In this study, 3T3-L1 cells were induced adipogenic differentiation and then treated with CGA. We investigate the effect of CGA in inhibiting adipogenesis and evaluate its role in modulating Wnt10b (wingless integration1 10b), β-catenin, glycogen synthase kinase-3β (GSK-3β), and peroxisome proliferator-activated receptor γ (PPAR-γ) involved in the Wnt (wingless integration1)/β-catenin signaling pathway. Results. The result showed that after CGA treatment, lipid accumulation and TG level decreased significantly in 3T3-L1 cells, indicating that CGA could inhibit adipogenesis. In addition, CGA repressed the induction of adipocyte differentiation biomarkers as PPAR-γ, adipocyte protein 2 (aP2), fatty acid synthase (FAS), and lipoprotein lipase (LPL), and the secretion of GSK-3β in a dose-dependent manner upregulated the expression of β-catenin and Wnt10b both in gene and protein levels. Moreover, CGA induced phosphorylation of GSK-3β and promoted the accumulation of free cytosolic β-catenin in 3T3-L1 adipocytes. Conclusion. Overall, these findings gave us the implications that CGA inhibits adipogenesis via the canonical Wnt signaling pathway.